The perception of parental rearing in Mexican adolescents: a qualitative review - Oudhof van Barneveld, Hans (2024)
The interaction of children with their parents acquires distinct characteristics when they enter into the stage of adolescence. The aim of the study was performing a narrative review of recent research among Mexican adolescents regarding their perception of parenting. The analysis was performed from the children’s perspective and by means of the assessment of contrasts in the results reported in articles and book chapters published in the last fifteen years. It was found that the adolescents who participated in the reviewed studies consider that their parents frequently carry out their childrearing activities and that they take care of the distinct facets involved in this process. Several studies have reported correlations of the perception of parenting with diverse variables associated with psychological development in adolescents. It is concluded that childrearing is a dynamic and complex process, which requires the study of diverse factors that intervene in the interaction between parents and children.